A deletion mutation in bovine SLC4A2 is associated with osteopetrosis in Red Angus cattle - Beever Jonathan E (BMC Genomics, 2010)
Abstract Background Osteopetrosis is a skeletal disorder of humans and animals characterized by the formation of overly dense bones, resulting from a deficiency in the number and/or function of bone-resorbing osteoclast cells. In cattle, osteopetrosis can either be induced during gestation by viral infection of the dam, or inherited as a recessive defect. Genetically affected calves are typically aborted late in gestation, display skull deformities and exhibit a marked reduction of osteoclasts. Although mutations in several genes are associated with osteopetrosis in humans and mice, the genetic basis of the cattle disorder was previously unknown. Results We have conducted a whole-genome association analysis to identify the mutation responsible for inherited osteopetrosis in Red Angus cattle. Analysis of >54,000 SNP genotypes for each of seven affected calves and nine control animals localized the defective gene to the telomeric end of bovine chromosome 4 (BTA4). Homozygosity analysis refined the interval to a 3.4-Mb region containing the SLC4A2 gene, encoding an anion exchanger protein necessary for proper osteoclast function. Examination of SLC4A2 from normal and affected animals revealed a ~2.8-kb deletion mutation in affected calves that encompasses exon 2 and nearly half of exon 3, predicted to prevent normal protein function. Analysis of RNA from a proven heterozygous individual confirmed the presence of transcripts lacking exons 2 and 3, in addition to normal transcripts. Genotyping of additional animals demonstrated complete concordance of the homozygous deletion genotype with the osteopetrosis phenotype. Histological examination of affected tissues revealed scarce, morphologically abnormal osteoclasts displaying evidence of apoptosis. Conclusions These results indicate that a deletion mutation within bovine SLC4A2 is associated with osteopetrosis in Red Angus cattle. Loss of SLC4A2 function appears to induce premature cell death, and likely results in cytoplasmic alkalinization of osteoclasts which, in turn, may disrupt acidification of resorption lacunae.